The Role of Regional Regulations in Optimizing Public Order, Public Order, and Community Protection (TATOHI: Jurnal Ilmu Hukum, 2025)
Introduction: The regulation of public order and community protection is essential in urban governance, especially in cities experiencing rapid social changes. Yogyakarta City Regional Regulation Number 7 of 2024 concerning the Implementation of Public Order, Community Protection, and Peace serves as a legal framework aimed at fostering an orderly, safe, and participatory urban environment.Purposes of the Research: The purpose of this study is to examine the normative legal basis, institutional implications, and socio-cultural impact of the regulation, as well as its effectiveness in supporting local initiatives to maintain public order and promote legal awareness in the community.Methods of the Research: The research method used in this article is normative juridical, focusing on the analysis of legal norms and their application through statutory, conceptual, and comparative approaches. Legal materials are obtained from legislation, official documents, and scholarly sources, and analyzed qualitatively to evaluate the implementation and implications of the regulation.Findings of the Research: The findings of this study show that the regulation not only strengthens the authority of law enforcement but also promotes community participation through the innovative Model Kampung Panca Tertib program. The five pillar Orderly Buildings, Orderly Roads, Orderly Business, Orderly Environment, and Orderly Society serve as tools to develop a sustainable legal culture at the grassroots level. However, the success of the regulation largely depends on institutional capacity, consistent community engagement, and long-term support from local government actors. Collaboration among stakeholders is essential to realize inclusive and civilized public order.